Hedging Expressions as Diplomatic Strategies in Joe Biden’s Speeches at the 78th and 79th Sessions of the UN General Assembly - Noki Septia Artiva (Universitas Muhammadiyah Mataram, 2026)
Political speeches require speakers to communicate carefully, especially in international forums involving diplomatic relations and global cooperation. One of the linguistic strategies used to achieve this goal is hedging expressions. This study aims to identify the types of hedging expressions, analyze their functions, and explain their role as diplomatic strategies in Joe Biden's speeches at the UN General Assembly. This study uses a qualitative approach with data sources in the form of official transcripts of Joe Biden's speeches at the 78th and 79th UN General Assembly sessions. The data were analyzed using the hedging expressions theory by Salager-Meyer (1997) and the diplomacy theory by Berridge (2015). The results show that there are 59 hedging expressions consisting of approximators (29), modal auxiliary verbs (22), introductory phrases (5), modal lexical verbs (1), adjectival modal phrases (1), and compound hedges (1), while if-clauses were not found. Hedging expressions have five functions, with the function of expressing uncertainty being the most dominant. In the context of diplomacy, hedging expressions serve to encourage international negotiations and dialogue, build cooperation and consensus, and maintain diplomatic relations. These findings indicate that hedging expressions are not only a linguistic tool for expressing uncertainty but also an effective diplomatic strategy in conveying sensitive issues in international forums.